2010
DOI: 10.1364/oe.18.010762
|View full text |Cite
|
Sign up to set email alerts
|

Non-contact, automated cardiac pulse measurements using video imaging and blind source separation

Abstract: Remote measurements of the cardiac pulse can provide comfortable physiological assessment without electrodes. However, attempts so far are non-automated, susceptible to motion artifacts and typically expensive. In this paper, we introduce a new methodology that overcomes these problems. This novel approach can be applied to color video recordings of the human face and is based on automatic face tracking along with blind source separation of the color channels into independent components. Using Bland-Altman and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
982
2
12

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 1,332 publications
(1,001 citation statements)
references
References 33 publications
5
982
2
12
Order By: Relevance
“…Facial video recording using the smartphone camera is a novel method of detecting a pulsatile facial photoplethysmographic signal without physical contact,18, 19, 20 with the potential for distant screening. A small proof‐of‐concept study supported the feasibility of such a contact‐free method for AF detection,19 but the performance of facial photoplethysmography for the detection of AF in a prospective study has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Facial video recording using the smartphone camera is a novel method of detecting a pulsatile facial photoplethysmographic signal without physical contact,18, 19, 20 with the potential for distant screening. A small proof‐of‐concept study supported the feasibility of such a contact‐free method for AF detection,19 but the performance of facial photoplethysmography for the detection of AF in a prospective study has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Early experiments have confirmed the viability of this technique (Poh et al, 2010;Farley et al, 2011;Poh et al, 2011). …”
Section: Absorption Coefficientmentioning
confidence: 89%
“…Very recently, measuring BVP and HRV signals from facial video data recorded by webcam and smart phones have been proposed in [4,5]. A summery about using smart phones to measure several physiological parameters can be found in [6].…”
Section: Related Workmentioning
confidence: 99%